(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
The use of different didactics methodologies and modalities is shown to be a valid and promising strategy in an attempt to address the individual differences of students with regard to the way they learn and appropriate the contents covered in the classroom. The aim of this study is to carry out a literature review based on studies that aim to promote meaningful learning through the application of the didactic sequence in mathematics classes.